Leverage, Sales Growth, and Firm Value: The Moderating Role of Profitability in Indonesia's Food and Beverage Subsector (2019–2023) - Isnaeni, Nazwaa Salsabila; Abdurrohim, Abdurrohim (International Journal of Education, Management, and Technology, 2025)
The Indonesian food and beverage sector contributed 33.72% to national industrial GDP in 2024 (BPS, 2024), underscoring its strategic economic role amid challenges such as macroeconomic volatility, regulatory changes, and shifting consumer preferences. Despite its significance, limited empirical research examines how leverage and sales growth affect firm value when moderated by profitability. This study investigates these relationships using secondary data from 20 food and beverage companies listed on the Indonesia Stock Exchange (IDX) between 2019 and 2023. Employing panel data regression with a Random Effect Model (REM) and Moderated Regression Analysis (MRA), the results show that leverage has a significant positive effect on firm value (β = 2.19, p < 0.05), while sales growth has no significant effect. Profitability significantly moderates the leverage–firm value relationship, with high-leverage, high-profit firms achieving greater market valuation, but does not moderate the sales growth–firm value relationship. These findings highlight profitability as a key factor that amplifies the positive effects of debt on firm value, whereas revenue growth alone does not enhance market valuation. The study offers practical implications for managers, investors, and policymakers in optimizing capital structure under volatile market conditions, and recommends incorporating macroeconomic variables and cross-sectoral data in future research for broader applicability. Keywords: Leverage; Sales Growth; Profitability; Firm Value; Panel Data Regression